The Invisible Mustahik: Exploring Social Exclusion and Barriers to Zakat Access for Prostitutes in Yogyakarta's Digital Space - Furqonul Haq; Athira Salsabila (Yayasan Darussalam Bengkulu, 2025)
This study aims to analyze the social exclusion of 11 digital prostitutes in Yogyakarta as